Humorous Coping With Unrequited Love: Is Perspective Change Important? - Greve, Werner; Hauser, Johanna; Rühs, Farina (Frontiers in Psychology, 2021)
A large number of studies suggest that humor is effective as a means of coping. However, it is less well understood which mechanisms are effective for this particular function of humor. The present study examines whether processes of change of perspective could be an effective coping-factor when facing unrequited love as a specific burden. In a questionnaire study, N = 148 persons aged 18-65 years (w = 96) with actual or past experiences of unrequited love reported on their subjective burden due to this experience, their self-esteem and satisfaction with life, two scales for humor (MSHS, Humorous Change of Perspective) and a coping scale characterized by a change of perspective in the confrontation with goal blockages (flexible goal adjustment). Results indicated that burden of unrequited love and both indicators of well-being were negatively associated. Multiple regression analyses showed that humor was a significant moderator of this relationship in nearly all combinations of operationalizations of humor and indicators of well-being: Higher levels of humor are associated with better well-being despite high expression of the burden. In addition, the study examined whether the coping effect of humor can be partly or mainly attributed to the individual’s capacity and willingness to change perspectives as captured by FGA. When including FGA as a covariate in the regression models, the moderation effect for MSHS did not persist. However, the moderator effect of humorous change of perspective proved to be independent of goal flexibility. Taken together the results suggest that perspective-changing skills play a significant role in the coping effect of humor in dealing with psychological burdens. However, depending on which humor facet is measured, the entailed perspective change may or may not appear to go beyond what the individual’s Flexible Goal Adjustment capability can account for. This suggests that humorous change of perspective in its coping effect includes aspects that are also discussed for other coping resources as well as its own, humor-specific aspects. Potential conclusions for further studies are discussed with respect of the necessity for replication and extension of the present study and to potential palliative effect of other facets of humor.